Assessing Water Deficit Induced Water Stress of Households and their Welfare in Small Cities of Nepal - Bista, Raghu Bir; Thakuri, Sudeep; Koirala, Prakirti; Bhattarai, Arun (Economic Journal of Development Issues, 2024)
This study investigates water deficit-induced stress in 12 small cities within Nepal’s Marshyangadi River Basin, crucial for sustainable water management amid global water scarcity concerns. Employing the Milankovitch Theory, it explores Earth-Sun relationships and their impact on long-term climate changes, shaping societal adaptation strategies. Utilizing the Water Deficit Model, the study unveils the multifaceted consequences of water scarcity of Gandaki Province’s Marshyangdi River basin. The study employs a comprehensive design, sampling 317 households across diverse ecological zones and elevations. The study finds the existing month-long water deficit in these cities to the higher water demand of households, along with water stress in the cities of Himal and Terai more than in the Hill. Water deficit is higher in Himal than in Hill and Terai because of lower water availability in Himal (below average 0.9). The people of Himal and Terai have extremely high stress but the people of Hills are comfortable without stress, except in Bandipur for drinking and cleanliness. In the 20 litres per capita per day water, water stress is found mixed. Five small cities in Himal and Terai are extremely stressed, meanwhile, 7 small cities in the Hill are not stressed, except two cities, Bandipur and Marshangdi. Relatively, the water deficit in the Hill is less than Himal and Terai. Similarly, in 20 liters per capita per day water, it is good for households but most cities have extreme water stress. The Hill’s water stress is lower than that of the Himalayan and Terai. By WHO’s standard (50 liters-100 liters per day per capita), all cities are extremely water deficient and critically water stressed. The findings reveal a direct correlation between water deficit and stress, impacting survival, hygiene, and living standards. The study concludes that despite ample water resources, poor governance and inadequate policies contribute to extreme water deficit, challenging SDG targets and living standards. It urges urgent action, accountability, budgeting, and a comprehensive plan for water poverty reduction.